2019
DOI: 10.3399/bjgp19x706625
|View full text |Cite
|
Sign up to set email alerts
|

Non-attendance at urgent referral appointments for suspected cancer: a qualitative study to gain understanding from patients and GPs

Abstract: BackgroundThe 2-week-wait urgent referral policy in the UK has sought to improve cancer outcomes by accelerating diagnosis and treatment. However, around 5–7% of symptomatic referred patients cancel or do not attend their hospital appointment. While subsequent cancer diagnosis was less likely in non-attenders, those with a diagnosis had worse early mortality outcomes.AimTo examine how interpersonal, communication, social, and organisational factors influence a patient’s non-attendance.Design and settingQualita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(50 citation statements)
references
References 27 publications
0
50
0
Order By: Relevance
“…A study of GPs found that most were aware that time constraints within consultations with older adults limited what could be discussed. 60 Two studies highlighted problems with policies such as ‘one appointment, one problem’, which may not suit an older patient demographic. 74 , 75 However, there was evidence that GPs considered the practicalities of older adults attending appointments, with one GP suggesting that older adults may find afternoon appointments easier.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of GPs found that most were aware that time constraints within consultations with older adults limited what could be discussed. 60 Two studies highlighted problems with policies such as ‘one appointment, one problem’, which may not suit an older patient demographic. 74 , 75 However, there was evidence that GPs considered the practicalities of older adults attending appointments, with one GP suggesting that older adults may find afternoon appointments easier.…”
Section: Resultsmentioning
confidence: 99%
“… 74 , 75 However, there was evidence that GPs considered the practicalities of older adults attending appointments, with one GP suggesting that older adults may find afternoon appointments easier. 60 …”
Section: Resultsmentioning
confidence: 99%
“…Sekhon et al ( 2017 ) highlights the centrality of self‐efficacy (an individual's confidence in their ability to perform the required behaviour) to the acceptability of an intervention. Previous findings (Jefferson et al, 2019 ) also identified difficulty booking a GP appointment as a barrier to early help‐seeking for suspected cancer symptoms. This suggests the need to examine the dynamics of patient‐provider communications while addressing the important elements that could facilitate or impede how ‘teachable moment’ is maximised in this context.…”
Section: Discussionmentioning
confidence: 89%
“…Their negative connotations for the healthcare industry impact heavily on patients and service provision. Within this review numerous adverse outcomes were associated with DNAs, including hospital penalties, increased waiting times (Jefferson et al. , 2019; Sheridan et al.…”
Section: Resultsmentioning
confidence: 99%
“…, 2021). Jefferson et al. (2019) identifies several key factors, such as system flaws and doctor-patient communication, as core complications of practice factors in their qualitative study.…”
Section: Resultsmentioning
confidence: 99%